Number attraction affects reanalysis in sentence processing. Issue 1 (2nd January 2018) - Suckow, Katja; van Gompel, Roger P. G.
ABSTRACT: Many studies have shown evidence for number attraction effects in production. Recent cross-linguistic findings suggest that number attraction can also affect comprehension of ungrammatical sentences. We present an eye-tracking experiment that investigates number attraction during recovery from garden-path sentences. The sentences contrasted locally ambiguous with unambiguous structures containing a plural or a singular attractor noun before a singular verb. Reading time data from the experiment suggest that number attraction effects occur when the processor has difficulty finding a grammatical analysis: Sentences with a local ambiguity had longer regression-path times when there was a plural number attractor than when there was a singular number attractor. The attractor number did not affect the processing of the unambiguous sentences.